2021
DOI: 10.1371/journal.pone.0255389
|View full text |Cite
|
Sign up to set email alerts
|

Methods for dealing with unequal cluster sizes in cluster randomized trials: A scoping review

Abstract: In a cluster-randomized trial (CRT), the number of participants enrolled often varies across clusters. This variation should be considered during both trial design and data analysis to ensure statistical performance goals are achieved. Most methodological literature on the CRT design has assumed equal cluster sizes. This scoping review focuses on methodology for unequal cluster size CRTs. EMBASE, Medline, Google Scholar, MathSciNet and Web of Science databases were searched to identify English-language article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Unbalanced sample sizes have been reported in various clinical fields. 16,17 For the adjustments of crowns, the Shapiro-Wilk Test was utilized to assess the normal distribution of maximum occlusion adjustment, area of occlusion adjustment, maximum mesial adjustment, and maximum distal adjustment. None of these variables followed a normal distribution, thus the nonparametric Kruskal-Wallis test was subsequently performed.…”
Section: Discussionmentioning
confidence: 99%
“…Unbalanced sample sizes have been reported in various clinical fields. 16,17 For the adjustments of crowns, the Shapiro-Wilk Test was utilized to assess the normal distribution of maximum occlusion adjustment, area of occlusion adjustment, maximum mesial adjustment, and maximum distal adjustment. None of these variables followed a normal distribution, thus the nonparametric Kruskal-Wallis test was subsequently performed.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether multilevel analyses were required to handle the nested structure of the data, i.e., multiple children within families, we calculated the intraclass correlation coefficient and design effects based on both the average and maximum cluster size (Zhan et al, 2021). The intraclass correlations (ranging from.43 for parental self-efficacy play to.71 for parenting stress) and design effects (ranging from 1.09 to 1.26 based on average cluster size and from 1.66 to 3.12 based on maximum cluster size) indicated that multilevel models should be used to account for the nested structure of the data (Hox & Maas, 2002;Vajargah & Nikbakht, 2015).…”
Section: Analytic Strategymentioning
confidence: 99%
“…We also computed design effects based on the maximum cluster size, because the use of average cluster size might result in an underestimation of the design effect (Zhan et al, 2021). The intraclass correlations (.39 for child social competence at 30 months)…”
Section: Analytic Strategymentioning
confidence: 99%